AJARAN MORAL KERIS JAWA - Nurhadi Siswanto (Institut Seni Indonesia Yogyakarta, 2013)
Java is so exotic. Java is beautiful. Being a Javanese as well as being any ethnicity, isnot a curse but a gift from God. Cultural values and wisdom not just tales of the parents alone,but it is a fact. One thing that is quite interesting to examine the Javanese is the existence of anheirloom called